1978
DOI: 10.1159/000181394
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of Tendons

Abstract: Rupture of ten major tendons occurred in 7 out of a total of 50 renal patients treated by chronic hemodialysis, in two renal units. The rupture occurred spontaneously without any special strain. Rupture was complete in five tendons and incomplete in the other five. In 2 cases, rupture occurred simultaneously in both quadriceps tendons. In 1 case a single quadriceps and a triceps brachii tendon were affected together. In 3 cases one quadriceps tendon was affected and in the last case, one triceps brachii tendon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…When fibrinoid degeneration occurs in the ligamentous or tendinous structure with inflammatory cells, some vessels are thrombosed. This ischemic change can be a predisposing factor for spontaneous rupture [9]. Additionally, the urate crystals themselves may cause a reduction in tensile strength of the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…When fibrinoid degeneration occurs in the ligamentous or tendinous structure with inflammatory cells, some vessels are thrombosed. This ischemic change can be a predisposing factor for spontaneous rupture [9]. Additionally, the urate crystals themselves may cause a reduction in tensile strength of the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic renal failure is considered to be the most frequently encountered risk factor in simultaneous QTR with a reported rate of more than 40% [28]. In renal patients incidence of QTR seems to be correlated to the duration of the disease, which contributes to the weakening of the tendon's ultrastructure by connective tissue elastosis and disturbance of the ground substance; primary or secondary hyperparathyroidism additionally may yield in weakening at the osteotendineous junction [16, 22, 23]. The fact that in our review obesity was found most frequently among risk factors (21.4%), might be explained by the selected group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mont et al published a case of hypocalcemic tetany resulting in bilateral QTR and unilateral TTR, but this is considered a spontaneous and not a traumatic tendon rupture [ 7 ]. A combination of QTR and TTR was described by Lotem et al, but they did not adequately document whether the lesions were complete or incomplete and whether they were simultaneous or sequential [ 11 ]. Despite the fact that many cases of single, bilateral, or even sequential tendon ruptures have already been described in the literature, we consider our case a novel presentation of traumatic quadriceps and triceps tendon rupture associated with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%